2007
DOI: 10.1002/pon.1155
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory, interview study of oncology patients' and health‐care staff experiences of discussing resuscitation

Abstract: There is little research about how patients and their families would like discussions surrounding resuscitation to take place. The purpose of this exploratory study was to investigate the experience of a discussion of resuscitation from the perspective of the participants. In-depth interviews were undertaken with 21 patients, of whom nine were interviewed together with a relative and 14 staff in an oncology setting. Data were analysed using a constant comparative method and coded using NVIVO qualitative data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…17,32 Furthermore, they are associated with better understanding of prognosis, 33 better family satisfaction with care, 8 and better quality of life. [34][35][36] However, despite these findings, these discussions often take place late in a patient's care, if at all. 37 Although many factors are not under the control of the oncologist, research has identified physician decision making, including inadequate physician communication and not recognizing the patient as dying, as the most frequently identified cause of late hospice referrals by patients' bereaved family members.…”
Section: Discussionmentioning
confidence: 99%
“…17,32 Furthermore, they are associated with better understanding of prognosis, 33 better family satisfaction with care, 8 and better quality of life. [34][35][36] However, despite these findings, these discussions often take place late in a patient's care, if at all. 37 Although many factors are not under the control of the oncologist, research has identified physician decision making, including inadequate physician communication and not recognizing the patient as dying, as the most frequently identified cause of late hospice referrals by patients' bereaved family members.…”
Section: Discussionmentioning
confidence: 99%
“…Cox et al 11 highlighted the scarcity of evidence about how patients and families would like discussions surrounding CPR to take place. Fear of causing distress and removing hope from patients are common reasons for not discussing CPR decisions with terminally ill patients 12 13.…”
Section: Discussionmentioning
confidence: 99%
“…Semi‐structured interviews were implemented since they represented the best method of obtaining the information required for the study. They made it easier for interviewees to use their own definitions of the issues, thus allowing the researcher to pursue the topics of interest . Interviews were conducted by two researchers in pairs, a psychologist and a pharmacist.…”
Section: Methodsmentioning
confidence: 99%